Ethnolinguistic Dimensions of the Korolele Ceremony: Ritual Language for Character Education - Ni Ketut Widhiarcani Matradewi; Loso Judijanto; Made Ayu Anggreni; Fahruddin Fahruddin; Arif Saefudin (Journal of Innovation in Educational and Cultural Research, 2025)
This study is motivated by the lack of ethnolinguistic studies exploring ritual language's role in traditional community character education. The purpose of the study is to analyse the verbal symbolism in ritual language and how the language is used as an informal educational tool. This study used a qualitative approach with ethnolinguistic methods. Data were collected through in-depth interviews with elders and ritual performers, participatory observation, and document study related to the oral tradition of the Dawan community. Data analysis was conducted using thematic and semiotic analysis to identify patterns of ritual language use. The findings show that ritual language in Korolele plays an important role in transmitting cultural values, such as solidarity, respect, and communal responsibility, to the younger generation. Language is a communication tool and a mechanism to internalise moral values and strengthen the community's collective identity. The ritual language in Korolele ceremonies is an effective instrument of culture-based character education, maintaining the continuity of oral traditions amidst modernisation. This study makes an important contribution to the study of ethnolinguistics, culture-based character education, and as a relevant informal education tool in traditional communities.